2006
DOI: 10.1892/0891-6640(2006)20[167:troami]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alveolar Macrophages in the Pathogenesis of Recurrent Airway Obstruction in Horses

Abstract: When challenged with allergens and pro-inflammatory agents, such as Aspergillus fumigatus (AF), hay dust solution (HDS) and lipopolysaccharide (LPS), the innate immune response will not only activate the immune system but also increase the amount of pro-inflammatory cytokines in the bronchoalveolar space. The aim of this study was to assess the response of equine alveolar macrophages to different aerosolized challenges and to investigate the differences in this response between horses susceptible or nonsuscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 38 publications
1
18
1
Order By: Relevance
“…Des‐CIC has anti‐inflammatory activity with affinity for the glucocorticoid receptor that is 100–120 times higher than the parent compound. The anti‐inflammatory effects of des‐CIC in human asthma are thought to be primarily mediated via inhibition of tumour necrosis factor‐alpha and the Th‐2 cytokine interleukin‐4 in airway epithelial cells , two cytokines implicated in the pathogenesis of equine asthma . The maximal dose of ciclesonide to be tested in the first study was based on the clinical equivalence observed in human patients between fluticasone propionate and ciclesonide (80 μg of ciclesonide are considered clinically equivalent to 100 μg of fluticasone ) and on previous experiments performed in horses during which fluticasone propionate was shown to be effective at doses ≥2000 μg/day .…”
Section: Discussionmentioning
confidence: 99%
“…Des‐CIC has anti‐inflammatory activity with affinity for the glucocorticoid receptor that is 100–120 times higher than the parent compound. The anti‐inflammatory effects of des‐CIC in human asthma are thought to be primarily mediated via inhibition of tumour necrosis factor‐alpha and the Th‐2 cytokine interleukin‐4 in airway epithelial cells , two cytokines implicated in the pathogenesis of equine asthma . The maximal dose of ciclesonide to be tested in the first study was based on the clinical equivalence observed in human patients between fluticasone propionate and ciclesonide (80 μg of ciclesonide are considered clinically equivalent to 100 μg of fluticasone ) and on previous experiments performed in horses during which fluticasone propionate was shown to be effective at doses ≥2000 μg/day .…”
Section: Discussionmentioning
confidence: 99%
“…Such dust is believed to cause chronic diseases especially related to lungs in cattle and horses. Laan and others (2006) have considered certain dust fractions to be the major cause for chronic and recurrent airway diseases in horses. Pulmonary mycosis, abortion, or mastitis has been reported in animals feeding on contaminated silage and hay (dos Santos and others 2003).…”
Section: Mycotoxins and Associated Health Risksmentioning
confidence: 99%
“…IL‐1β and TNF‐α are produced by alveolar macrophages of normal horses stimulated ex vivo by A. fumigatus , suggesting that molecular patterns of mould antigens may favour cellular activation independently of clinical diagnosis 139 . Conversely, alveolar macrophages isolated from heaves‐affected horses after inhalational challenges with endotoxin or HDS were found to have higher expression of TNF‐α (HDS), IL‐1β and IL‐8 (endotoxin) than those of controls 140 . Early IL‐17 and MIP‐2 expression by pulmonary mononuclear cells in response to ex vivo stimulation with soluble hay dust also appears to discriminate between control and heaves‐affected horses as reported in another study 141 .…”
Section: Airway Inflammationmentioning
confidence: 99%